Strategies for enhancing maize (Zea mays) productivity and profitability through integrated nutrient management in rainfed agro-ecosystems - DAYAL, PARMESWAR; MEENA, SAMRATH LAL; RATHORE, SANJAY SINGH; JAT, SANKAR LAL; KAUR, RAMANJIT; PRAJAPATI, SUNIL KUMAR; JENA, TWINKLE; MANDAL, ABHIJIT (The Indian Journal of Agricultural Sciences, 2026)
A field experiment was conducted during rainy (kharif) seasons of 2023 and 2024 at Research Farm of ICAR-Indian Agricultural Research Institute, New Delhi to study the effects of integrated nutrient management (INM) on productivity and profitability of rainfed maize (Zea mays L.) under maize–mustard (Brassica juncea L.) cropping system. The study comprised of ten INM treatments, including absolute control, sole recommended dose of nitrogen (RDN) and combinations of inorganic fertilisers with farmyard manure (FYM), leaf compost (LC) and crop residues (CR) replicated thrice in randomised complete block design. The combination of 50% RDN + FYM (2.0 t/ha) + LC (2.0 t/ha) recorded the highest cob length (15.2–16.1 cm), cob girth (8.54–8.66 cm), 1000-grain weight (255.1–258.2 g), grain yield (5.53–5.62 t/ha), stover yield (9.21–9.35 t/ha) and biological yield (14.74–14.98 t/ha). This treatment produced 35% and more than 110% higher grain yield compared to 100% RDN and absolute control, respectively. It also exhibited maximum gross returns (+131.4%), net returns (+231.3%) and net benefit-cost ratio (+185.8%) based on the two-year mean. The treatment T6 consistently recorded the highest N uptake (1.73–152.2%), P uptake (0.55– 185.5%) and K uptake (5.5–136%) by grain and stover, respectively over other treatments. Various yield attributing characters, 1000-seed weight, cob length and cob girth demonstrated significantly higher positive correlation with grain yield. The study concluded that integrated nutrient management with 50% RDN + FYM + LC is a highly productive, economically viable and sustainable strategy for rainfed maize cultivation in the Indo-Gangetic Plain region (IGPR), reducing reliance on chemical fertilisers and enhancing long-term soil fertility and sustainability.